Selective association of the trout-specific H6 protein with chromatin regions susceptible to DNase I and DNase II: possible location of HMG-T in the spacer region between core nucleosomes. - Levy W, B (1977)
Nuclei and chromatin from trout testis cells were digested with three different nucleases (DNase I, DNase II, and micrococcal nuclease), and the acid-soluble proteins that were solubilized and those remaining bound to the nuclease-resistant DNA were compared electrophoretically. With the conditions described by H. Weintraub and M Groudine [(1976) science, 193, 848-856], which we previously found to be selective in digesting actively transcribed regions in trout testis chromatin, a single chromosomal protein, H6, was solubilized. The nucleosomal histones and H1 remained insoluble, bound to the resistant DNA. In contrast, digestion with micrococcal nuclease led to a preferential solubilization of a second protein, HMG-T, together with the release of some nucleosomal histones and H1 into the soluble fraction. DNase II also discriminated between "active" and "inactive" chromatins; when a DNase II-solubilized "active" chromatin fraction was prepared, it too was enriched in H6 and HMG-T. Thus, both H6 and HMG-T, the two major low-salt extractable chromosomal nonhistone the two major low-salt extractable chromosomal nonhistone proteins from trout testis, are associated with chromatin regions selectively sensitive to nucleases. The preferential solubilization of HMG-T by micrococcal nuclease action suggests that it might be located at the internucleosomal "spacer" region.